NILAI PENDIDIKAN KARAKTER DAN KONSEP PENDIDIKAN RA KARTINI PADA CERITA RAKYAT VOLUME EMPAT - Rima Karima Rhamdon; Prima Gusti Yanti (Universitas Muhammadiyah Surakarta, 2021)
The study aims to determine the value of character education and the concept of RA Kartini’s education in collection of folktale volume four. The research method used is descriptive qualitative. The data source for this research is a collection of folktales volume four. The data collection technique used is text analysis. The data in this study were analyzed by reading the entire content of the folktale, marking and identifying the character education values and educational concept of RA Kartini contained in the folktale. The next step is to analyze and conclude the result of the analysis of the value character education and concept of RA Kartini’s education. The result showed that the value of character education and concept RA Kartini’s education, which was seen through the words of character, events and behavior of the character in volume four folklore were seen in five aspects of the value of character education including religious, mutual cooperation, independence, integrity, and nationality. While RA Kartini’s five educational concept include women as the first educators, women as carriers of civilization, education that educates the main and soul, gender equality, and love for the homeland. That’s because this fourth volume of folklore can be used as an increase of character values so that it can be applied in everyday life. The five educational concepts of RA Kartini in this folklore can be described as that women have the same rights and obligations in world civilization.Keywords: the value of character, RA Kartini’s concept education, folktale